2012
DOI: 10.1111/j.1573-7861.2012.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Justice and Reactions to Coercive Computers1

Abstract: Sociology and justice theories indicate that coercive behavior creates a sense of injustice, but what if a computer is the proximal source of this coercion? I argue that people attribute justice to computers, but do so differently than to humans-people may perceive computers' behavior as unjust, but not as unjust as the same behavior by humans. Likewise, individuals resist and retaliate against coercive behavior, but do so less if the coercer is a computer. These hypotheses are extended from justice studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…When the partner is a computer, participants might conclude that a machine cannot intentionally behave in an unjust manner and is therefore less deserving of retribution. Although Shank (2012) proposed several mechanisms to explain his findings, the results largely support what was predicted by his treatment of mindlessness, and we expect a similar process to occur when participants interact with a selfish partner. Hypothesis 2 predicts that selfish behaviors by partners will ''break'' the mindlessness of participants because such behavior is not normatively expected, and that a closer evaluation of the partner's identity may lead participants to behave more generously toward partners that are described as computers instead of humans.…”
Section: Predictionssupporting
confidence: 80%
See 2 more Smart Citations
“…When the partner is a computer, participants might conclude that a machine cannot intentionally behave in an unjust manner and is therefore less deserving of retribution. Although Shank (2012) proposed several mechanisms to explain his findings, the results largely support what was predicted by his treatment of mindlessness, and we expect a similar process to occur when participants interact with a selfish partner. Hypothesis 2 predicts that selfish behaviors by partners will ''break'' the mindlessness of participants because such behavior is not normatively expected, and that a closer evaluation of the partner's identity may lead participants to behave more generously toward partners that are described as computers instead of humans.…”
Section: Predictionssupporting
confidence: 80%
“…Shank (2012) suggested that disrupting this process of mindlessness by having participants encounter normatively unexpected behaviors from their partners would provide such motivation. This argument leads to our first hypothesis, predicting that participants will behave no differently toward human or computerized partners who behave generously toward them because generosity is normatively expected in this situation.…”
Section: Predictionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, nonhuman actors, such as organizations, are often seen as agentic. For example, computer actors elicit similar emotional responses to those eUcited by human actors (Ferdig and Mishra 2004;Shank 2012). People can attribute intentionality to organizations due to their perceived agency.…”
Section: Organizational Causesmentioning
confidence: 95%
“…Bisher wurden Gerechtigkeitswahrnehmungen fast ausschließ-lich in der Mensch-Mensch-Interaktion untersucht (für eine Ausnahme siehe (Shank 2012(Shank , 2014). Es gibt jedoch erste Überlegungen, wie Prinzipien der Gerechtigkeit auch in die Mensch-System-Interaktion übertragen werden können (vgl.…”
Section: Introductionunclassified